Pengaruh Variasi Konsentrasi Asam Asetat Terhadap Hasil Sintesis Nanokitosan Dengan Metode Gelasi Ionik - Dewita, Putri Aurora; Fadli, Ahmad; Sunarno, Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Industrial waste of dried shrimp shells contains chitin which can be used as raw material for chitosan synthesis. Along with the development of technology, product with using chitosan continues to be developed by physically modifying chitosan into nanochitosan so that it has a wider utilization than chitosan. This study was aimed to synthesize nanocitosan using the ionic gelation method and determine the effect of the acetic acid concentrations and sodium tripolyphosphate concentrations on the characteristics of nanochitosan. The procedure of nanochitosan synthesis by dissolved chitosan with acetic acid to obtain 0.2% chitosan solution and stirred with a magnetic stirrer. NaTPP solution with a chitosan volume ratio of NaTPP 5: 1 was added to the chitosan solution and stirred for 1 hour at a speed of 1200 rpm. Furthermore, the nanochitosan was characterized by using Particle Size Analyzer (PSA). The acetic acid concentrations used were 0.5% and 2%. The increase in acetic acid concentration (0.5% and 2%) with the constant of 0.5% NaTPP concentration causes the polydispersity index decrease (1.451 and 0.924). Keywords: acetic acid, ionic gelation, nanochitosan, sodium tripolyphosphate